Estudio de prefactibilidad para la instalación de una planta de producción de cubiertos y platos biodegradables a base de la fécula de maíz (Zea mays) - Bautista Jeri, Pierina Rufina (2023)
In Peru and in the world, the need to use plastics over the years has impacted the environment. Plastic waste pollution is one of the main environmental problems that we are experiencing today, this problem is one of the greatest environmental challenges that is affecting the 21st century. That is why the project's main motivation is to be part of the change to save the planet, to replace a product made from conventional plastics to one that is made from a natural resource, is biodegradable and eco-friendly with the environment. The purpose of this project is to evaluate the pre-feasibility of the installation of a plant to produce biodegradable plates and cutlery from cornstarch, establishing its technical, economic, market and social feasibility, considering a great opportunity and alternative for the industry of the plastics. The production of biodegradable plates and cutlery. It is an opportunity to meet expectations in environmental care. Eight study chapter, the calculation of the projected demand that is expected from this project will be presented. In that same chapter, the product, the target market and its characteristics will be described. In the chapter on plant location, the most feasible locations for the installation of the factory will be presented; Likewise, in the chapter on the evaluation of the plant size, the corresponding evaluations of the following factors will be carried out: resources, the market and technology.